Hollow porous carbon sphere ultra-black material and preparation method thereof

Through the core-shell structure and chemical etching method of phenolic resin and silica gel, hollow porous carbon ball super black material was prepared, which solved the problems of complex and high cost in the existing technology, and realized the simplified preparation process and improved the Visible light absorption effect.

CN119284883APending Publication Date: 2025-01-10CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE

Patent Information

Application Number
CN202411413255.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

Smart Images

  • Figure CN119284883A_ABST
    Figure CN119284883A_ABST
Patent Text Reader

Abstract

The invention provides a hollow porous carbon sphere ultra-black material and a preparation method thereof, the ultra-black material comprises phenolic resin, and the phenolic resin is prepared by synthesizing resorcinol and formaldehyde; the preparation method comprises the following steps: adding resorcinol and formaldehyde into a silicon dioxide gel solution to form a core-shell structure SiO2 (at) RF taking silicon dioxide as a core and phenolic resin as a shell; and carbonizing the core-shell structure SiO2 (at) RF in a nitrogen atmosphere at a high temperature to convert the phenolic resin shell layer into a carbon shell layer, removing silicon dioxide by using an etching agent, and forming pores in the carbon shell layer to obtain the hollow porous carbon sphere ultra-black material. According to the hollow porous carbon sphere ultra-black material and the preparation method thereof, on the basis of guaranteeing the light absorption performance of the carbon sphere ultra-black material, the preparation process of the material is simplified, and the preparation cost is reduced; and the intrinsic absorption of the prepared carbon sphere on visible light can be improved, and more reflection absorption can be obtained through structure adjustment, so that the hollow macroporous carbon sphere has an excellent absorption effect on visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon-based ultra-black materials, and in particular to a hollow porous carbon ball ultra-black material and a preparation method thereof. Background Art

[0002] At present, the research on carbon-based materials is the hottest in the research of ultra-black materials. Compared with other materials, carbon-based materials usually have superior broadband light absorption characteristics due to their unique band structure, that is, the intrinsic optical properties are mainly determined by π-band light transitions. In addition, with the development of low-dimensional carbon preparation technology, the preparation and structural regulation of carbon-based materials are now easier. Compared with other materials, carbon materials have lower density, more stable chemical properties, lower prices, and are easier to obtain.

[0003] Patent CN105819422A disclosed by Li Jiansheng et al. from Nanjing University of Science and Technology in 2016 provides a method for preparing nitrogen-doped hollow mesoporous carbon spheres, which can effectively control the size and morphology of hollow carbon nanospheres, with the particle size controlled within 550nm and the pore size within the mesoporous size (2.4-2.7nm).

[0004] In 2016, Zhu et al. from the China Academy of Engineering Physics prepared organic aerogels with different densities as low as 20 mg / cm by pyrolysis of organic aerogels formed by condensation of resorcinol and formaldehyde water. 3 The results show that the density of carbon aerogel is less than 70mg / cm 3 The total reflectivity of carbon aerogel in the wavelength range of 400-2000nm is usually less than 0.24%. There are relevant research reports at home and abroad.

[0005] In 2017, Francesco De Nicola et al. from the University of Rome Tor Vergata prepared a film (≈150nm) made of randomly arranged hierarchical carbon nanotube arrays (RAHCNAs), with an upper limit of 99.36% and a lower limit of 98.19% in the spectral range of 0.2-14μm. These achievements are due to the hierarchical surface morphology of RAHCNA, which provides a large effective area and graded refractive index. The former feature improves the RAHCNA absorptivity, absorbing broadband ultraviolet to infrared as the absorption length of the film is greatly reduced, while the latter attribute leads to broadband, omnidirectional, polarization-independent suppression of optical reflection through the moth-eye effect.

[0006] In 2019, Guo et al. from the University of Chinese Academy of Sciences used poly(vinylidene chloride-co-vinyl chloride) as a precursor to prepare layered porous carbon spheres. Desalination and chlorination treatment is crucial to the morphological robustness during the carbonization process. The hemispherical reflectivity of the carbon sphere material is less than 0.2% in the visible light range, less than 0.3% in the range of 300nm-2000nm, and the lowest reflectivity is 0.14%. This ultra-black coating has the advantages of easy use of starting materials, low equipment requirements, and high adaptability to various substrates.

[0007] In 2020, Guo et al. from the University of the Chinese Academy of Sciences prepared carbon vesicles (CVs) for solvent-processable ultra-black coatings. The manufacturing process includes template co-condensation of silica and resorcinol formaldehyde resin (RF resin), followed by carbonization and template removal. The synthesized structure shows a very thin inner layer, a rough outer layer, and a nanoporous interlayer. This structure introduces randomness and breaks the spherical symmetry of ordinary carbon hollow spheres. Therefore, structural color due to internal interference of particles is avoided. In addition, due to its low carbon filling rate and nanoscale scatterer size, it shows broadband low reflectivity. At 360nm, the lowest reflectivity reaches about 0.10%.

[0008] In 2023, Lin et al. from Huaqiao University proposed a new method using hot air to promote the formation of carbon nanotube (CNT) microstructure slurry on the surface of the coating. This method can produce ultra-black materials on a large scale at room temperature. The experimental results showed that the coating was successfully prepared, allowing direct exposure to the surface microstructure of the carbon nanotubes. Morphological characterization showed that a porous microstructure was obtained after spraying, resulting in more light scattering sites. These porous structures and light scattering sites play a vital role in achieving superior light absorption, with the average light absorption rate of the coating reaching 99.51%.

[0009] The above-mentioned research results have proven that the adjustment of the composition and structure of carbon materials can achieve good light absorption effects. However, since the above-mentioned adjustment process of the composition and structure of carbon materials is generally complicated and costly, it is of great significance to study how to simplify the material preparation process and reduce the preparation cost while ensuring the light absorption performance of carbon ball ultra-black materials. Summary of the invention

[0010] In view of this, the present invention aims to propose a hollow porous carbon sphere ultra-black material and a preparation method thereof, so as to solve the problems in the prior art that the carbon material composition and structure adjustment process are generally complicated and costly; thereby achieving the goal of simplifying the material preparation process and reducing the preparation cost on the basis of ensuring the light absorption performance of the carbon sphere ultra-black material; and while improving the intrinsic absorption of the prepared carbon spheres to visible light, more reflected absorption can be obtained through structural adjustment, thereby making the hollow macroporous carbon spheres have excellent absorption effect on visible light.

[0011] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0012] The invention relates to a hollow porous carbon sphere ultra-black material and a preparation method thereof. The hollow porous carbon sphere ultra-black material comprises a phenolic resin, wherein the phenolic resin is synthesized from resorcinol and formaldehyde; resorcinol and formaldehyde are added to a silica gel solution to form a core-shell structure SiO2@RF with silica as a core and the phenolic resin as a shell; the core-shell structure SiO2@RF is carbonized in a nitrogen atmosphere at high temperature to convert the phenolic resin shell layer into a carbon shell layer, the silica is removed by an etchant, and holes are formed in the carbon shell layer to obtain the hollow porous carbon sphere ultra-black material.

[0013] Furthermore, the etchant is sodium peroxide.

[0014] Furthermore, the amount of sodium peroxide used in the process of removing silicon dioxide is excessive.

[0015] Furthermore, in the silica gel solution, the particle size of silica with different particle sizes can be adjusted in the range of 70 nanometers to 2000 nanometers.

[0016] Furthermore, the preparation method of the hollow porous carbon ball ultra-black material is prepared by combining a hard template method and a chemical etching method.

[0017] A method for preparing a hollow porous carbon sphere ultra-black material, the method is applied to prepare the hollow porous carbon sphere ultra-black material, the method comprises the following steps:

[0018] Step 1, synthesis of silicon dioxide: prepare a silicon dioxide gel solution by a sol-gel method, and adjust the amount of ammonia water and the amount of potassium chloride added according to the required particle size of silicon dioxide to obtain silicon dioxide with different required particle sizes;

[0019] Step 2, synthesis of SiO2@RF: adding resorcinol and formaldehyde to the silica gel solution, the phenolic resin generated by resorcinol and formaldehyde will adhere to the surface of silica, forming a core-shell structure SiO2@RF with silica as the core and phenolic resin as the shell;

[0020] Step 3: Carbonization to form SiO2@C: The core-shell structure SiO2@RF is carbonized in a tubular furnace in a nitrogen atmosphere at high temperature, so that the phenolic resin shell layer is converted into a carbon shell layer SiO2@C;

[0021] Step 4: Removal of silica core: Add excess sodium hydroxide to remove silica in the carbon shell SiO2@C to obtain hollow carbon spheres;

[0022] Step 5: Sodium hydroxide pore formation: The dried hollow carbon spheres are mixed with sodium hydroxide and reacted at high temperature to form pores to obtain hollow porous carbon spheres.

[0023] Furthermore, in step 2, the thickness of the phenolic resin shell can be changed by changing the amount of resorcinol and formaldehyde, thereby obtaining hollow carbon spheres with different desired shell thicknesses.

[0024] Furthermore, in step five, during the pore-forming process, hollow porous carbon spheres with different pore sizes can be obtained by adjusting relevant parameters.

[0025] Furthermore, the relevant parameters include any one or more of the thickness of the carbon sphere shell, the temperature of the pore-forming reaction, and the ratio of the hollow carbon sphere to sodium hydroxide.

[0026] Furthermore, the pore size range of the hollow porous carbon spheres can be adjusted from micropores to mesopores and then to macropores; the pore size of the micropores is less than 10 nanometers; the pore size of the mesopores is between 10 nanometers and 50 nanometers; and the pore size of the macropores is greater than 50 nanometers.

[0027] Compared with the prior art, the hollow porous carbon ball ultra-black material and the preparation method thereof described in the present invention have the following beneficial effects:

[0028] By setting up the materials and methods, it is possible to simplify the material preparation process and reduce the preparation cost while ensuring the light absorption performance of the carbon sphere ultra-black material; it is also possible to improve the intrinsic absorption of the prepared carbon spheres to visible light while obtaining more reflective absorption through structural adjustment, thereby making the hollow macroporous carbon spheres have excellent absorption effects on visible light. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings, which constitute part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations of the present invention.

[0030] In the figure:

[0031] Figure 1 This is a schematic diagram of scanning electron microscopy of microporous hollow carbon spheres;

[0032] Figure 2 This is a schematic diagram of scanning electron microscopy of mesoporous hollow carbon spheres;

[0033] Figure 3 This is a schematic diagram of scanning electron microscopy of macroporous hollow carbon spheres;

[0034] Figure 4 Schematic diagram of the reflectivity of hollow carbon spheres with different particle sizes;

[0035] Figure 5 Schematic diagram of the reflectivity of hollow carbon spheres with different pore sizes. DETAILED DESCRIPTION

[0036] The inventive concepts of the present disclosure will be described below using terms commonly used by those skilled in the art to convey the essence of their work to other persons skilled in the art. However, these inventive concepts can be embodied in many different forms and should not be considered limited to the embodiments described herein.

[0037] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0038] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0039] In the prior art, carbon nanotubes are the most excellent super black materials, but their application conditions are relatively harsh, and the production process is also cumbersome and expensive. Carbon balls and carbon nanotubes, which are both carbon materials, have the same intrinsic absorption capacity, and the structure of carbon balls can be easily and carefully set to achieve multiple reflections of visible light to achieve the super black effect. Hollow macroporous carbon balls are an excellent structure among carbon balls. It can not only achieve the super black effect, but also have a more stable structure and simpler preparation, so the application conditions are more relaxed. It is applied to the surface of optical components to reduce reflection and improve the observation accuracy of optical equipment such as lasers, cameras, and telescopes. It can also be applied to military aircraft, vehicles and equipment to reduce visibility and improve stealth. It can also be applied to solar panels to improve the absorption efficiency of light, increase electrical energy output or be used in collectors and solar absorbers to improve the efficiency of solar thermal energy systems. However, the existing hollow macroporous carbon balls have the problems of complex preparation process and high preparation cost.

[0040] In order to solve the problem that the composition and structure adjustment process of carbon materials in the prior art are generally complicated and costly; this embodiment selects hollow carbon spheres as the research object, and develops a carbon sphere ultra-black material with a simple process by regulating the structure of the carbon spheres, namely the particle size and pore size; specifically, this embodiment proposes a hollow porous carbon sphere ultra-black material and a preparation method thereof, wherein the hollow porous carbon sphere ultra-black material includes phenolic resin (Resorcinol Formaldehyde, RF), which is synthesized from resorcinol and formaldehyde; resorcinol and formaldehyde are added to a silica gel solution to form a core-shell structure SiO2@RF with silica (SiO2) as the core and phenolic resin as the shell; the core-shell structure SiO2@RF is carbonized in a nitrogen atmosphere at high temperature to convert the phenolic resin shell layer into a carbon shell layer, and the silica is removed by an etchant, and holes are made in the carbon shell layer to obtain a hollow porous carbon sphere ultra-black material. Among them, the etchant is sodium peroxide (NaOH), and the amount of sodium peroxide used in the process of removing silica is excessive. In the silica gel solution, the particle size adjustment range of silica with different particle sizes is 70 nanometers-2000 nanometers. The preparation method of hollow porous carbon sphere ultra-black material is prepared by combining hard template method and chemical etching method. After the hollow carbon spheres are prepared by the hard template method, the hollow porous carbon spheres with different pore sizes are obtained by chemical etching, and finally the ultra-black carbon spheres with the best light absorption performance are screened out.

[0041] The hollow porous carbon spheres developed by the present application can greatly enhance the reflection of visible light inside the material. Coupled with the strong absorption of visible light by carbon materials, the absorption of visible light in the 400-760 nanometer band can reach 3.469%-1.881%.

[0042] A method for preparing a hollow porous carbon sphere ultra-black material, the method is applied to prepare the hollow porous carbon sphere ultra-black material, the method comprises the following steps:

[0043] Step 1, synthesis of silicon dioxide: prepare a silicon dioxide gel solution by a sol-gel method, and adjust the amount of ammonia water and the amount of potassium chloride added according to the required particle size of silicon dioxide to obtain silicon dioxide with different required particle sizes;

[0044] Step 2, synthesis of SiO2@RF: adding resorcinol and formaldehyde to the silica gel solution, the phenolic resin generated by resorcinol and formaldehyde will adhere to the surface of silica, forming a core-shell structure SiO2@RF with silica as the core and phenolic resin as the shell;

[0045] Step 3: Carbonization to form SiO2@C: The core-shell structure SiO2@RF is carbonized in a tubular furnace in a nitrogen atmosphere at high temperature, so that the phenolic resin shell layer is converted into a carbon shell layer SiO2@C;

[0046] Step 4: Removal of silica core: Add excess sodium hydroxide to remove silica in the carbon shell SiO2@C to obtain hollow carbon spheres;

[0047] Step 5: Sodium hydroxide pore formation: The dried hollow carbon spheres are mixed with sodium hydroxide and reacted at high temperature to form pores to obtain hollow porous carbon spheres.

[0048] Among them, in step 2, by changing the amount of resorcinol and formaldehyde, the thickness of the phenolic resin shell can be easily changed, so as to obtain hollow carbon spheres with different shell thicknesses required in the subsequent step. In step 5, during the pore-making process, the thickness of the carbon sphere shell, the temperature of the pore-making reaction, and the ratio of the hollow carbon sphere to sodium hydroxide will affect the size of the pores. Adjusting the relevant parameters can obtain hollow porous carbon spheres with different pore sizes; wherein the relevant parameters include any one or more of the thickness of the carbon sphere shell, the temperature of the pore-making reaction, and the ratio of the hollow carbon sphere to sodium hydroxide. The pore size range of the hollow porous carbon sphere can be adjusted from micropores to mesopores and then to macropores; the pore size of the micropores is less than 10 nanometers; the pore size of the mesopores is between 10 nanometers and 50 nanometers; the pore size of the macropores is greater than 50 nanometers.

[0049] Through the setting of the method, the material preparation process can be simplified and the preparation cost can be reduced on the basis of ensuring the light absorption performance of the carbon ball ultra-black material; while improving the intrinsic absorption of the prepared carbon ball to visible light, more reflection absorption can be obtained through structural adjustment, thereby making the hollow macroporous carbon ball have excellent absorption effect on visible light. In addition, sodium hydroxide is both a denuclearizing agent for removing silicon dioxide and a pore-forming agent for hollow carbon balls, which can effectively simplify the preparation process of hollow porous carbon balls and improve the preparation efficiency of hollow porous carbon balls; in addition, the carbon source selects phenolic resin as the shell, which can reduce the cost of raw materials for preparation.

[0050] Step one includes:

[0051] Step S11: 1000-2000 ml of anhydrous ethanol, 200-300 ml of deionized water, 40-80 ml of ethyl orthosilicate and ammonia water are added into a beaker and mixed and stirred for 10-60 minutes. After the reaction is completed, a white silica emulsion is obtained, i.e., a silica gel solution.

[0052] Step S12: Select and adjust the amount of ammonia water and the amount of potassium chloride added to obtain silicon dioxide with different required particle sizes. The adjustment range of ammonia water is 20ml-200ml, and the particle size of silicon dioxide in the silicon dioxide gel solution changes from 70nm to 400nm as adjusted by ammonia water.

[0053] Step 2 includes:

[0054] Step S21: adding 6-24 g of resorcinol and 8.4-33.2 ml of formaldehyde to the silica gel solution to obtain a first mixed solution;

[0055] Step S22: After the first mixed solution is stirred for reaction, the solid in the first mixed solution is extracted by centrifugation, and the solid is placed in an oven and dried at a preset drying temperature to obtain yellow SiO2@RF;

[0056] Step S23: Grind the yellow SiO2@RF into SiO2@RF powder using a mortar, wherein the preset drying temperature ranges from 60°C to 80°C.

[0057] Step three includes:

[0058] Step S31: putting SiO2@RF powder into a tube furnace, connecting nitrogen gas, and performing carbonization reaction at a preset temperature;

[0059] Step S32: The temperature in the tube furnace is naturally cooled to room temperature, and the carbonized black SiO2@C is taken out.

[0060] Wherein, in step S31, during the carbonization reaction, the preset temperature in the tubular furnace is 700°C-1000°C.

[0061] Step 4 includes:

[0062] Step S41: dissolving a slightly excess amount of sodium hydroxide in deionized water;

[0063] Step S42: adding SiO2@C to a sodium hydroxide solution, and heating and stirring to obtain a second mixed solution;

[0064] Step S43: After the reaction is completed, the second mixed solution is filtered and then washed at least once until the filtrate after washing is neutral, and the washing is completed to obtain the solid in the second mixed solution;

[0065] Step S44: drying the solid in an oven at a preset drying temperature of 60° C.-80° C. and then grinding the solid in a mortar to form a powder, wherein the powder is hollow carbon spheres (HCS).

[0066] Step 5:

[0067] Step S51: adding hollow carbon spheres and sodium hydroxide in different mass ratios into a beaker;

[0068] Step S52: adding deionized water and ethanol into a beaker, and uniformly mixing the hollow carbon spheres and sodium hydroxide with the deionized water and ethanol to form a third mixed solution;

[0069] Step S53: After subjecting the third mixed liquid to ultrasonic treatment, the third mixed liquid is placed in an oven for drying;

[0070] Step S54: Grind the solid in the dried third mixed solution evenly with a mortar, put it into a tube furnace, react at a preset temperature of 700-1000° C., and then take out the solid after cooling it to room temperature in the tube furnace;

[0071] Step S55: The solid in the third mixed liquid taken out from the tube furnace is washed at least once until the filtrate is neutral, and then put into the oven again for drying, and the dried solid is ground into powder to obtain hollow porous carbon spheres.

[0072] Wherein, in step S51, the preset range of different mass ratios of the selected hollow carbon spheres is 3:1-1:1.

[0073] Through the synthetic route of first preparing the core-shell structure and then removing the core in this application, the desired structure of the hollow carbon sphere is obtained. On this basis, various parameters of the reaction are adjusted to successfully synthesize hollow carbon spheres of different particle sizes and different pore sizes. Then, through the action of sodium hydroxide, the desired hollow porous carbon spheres are synthesized, and the structure of the carbon spheres is optimized so that more visible light enters the interior of the carbon spheres with multiple reflection losses. In addition, the synthesis cost of this type of ultra-black material is low, the synthesis method is simple, the operation is simple, the light absorption performance is excellent, and it has a wider range of applications than other ultra-black carbon materials. It has broad application prospects in optical applications, thermal control, energy fields, and stealth technology.

[0074] Example 1

[0075] Step 1: Add 1000-2000 ml of anhydrous ethanol, 200-300 ml of deionized water, 40-80 ml of ethyl orthosilicate and 70 ml of ammonia water into a beaker, mix and stir to prepare a silica gel solution.

[0076] Step 2: Add 18 g of resorcinol and 25.2 ml of formaldehyde to the silica emulsion, i.e., the silica gel solution, and continue to stir and react to obtain SiO2@RF, which is then ground into powder using a mortar.

[0077] Step 3: Put the ground SiO2@RF powder into a tube furnace, connect nitrogen, and carbonize at 1000°C. When the temperature in the tube furnace naturally cools down to room temperature, take out the black SiO2@C.

[0078] Step 4: Take a slightly excess amount of sodium hydroxide and dissolve it in deionized water, then add SiO2@C to the sodium hydroxide solution, heat and stir, and then filter the solution after the reaction and wash it several times until the filtrate is neutral. After washing, dry the obtained solid in an oven at 60-80°C. After drying, grind the solid into powder to obtain hollow carbon spheres (HCS).

[0079] Step 5. Take the hollow carbon spheres and sodium hydroxide and add them to a beaker. Add deionized water and ethanol to mix the hollow carbon spheres and sodium hydroxide evenly. Put them into a tubular furnace and heat them to 700-1000°C for reaction. After the temperature in the tubular furnace cools to room temperature, take out the solid, wash the solid to neutrality and put it in an oven to dry. Finally, grind the solid into powder to obtain hollow porous carbon spheres.

[0080] After testing the sample, it can be concluded according to the test results: the reflectivity of the sample in the visible light band (400nm-760nm) is 9.896%-4.157%, while the reflectivity of the commercially available carbon powder as a comparison example in the visible light band (400nm-760nm) is 13.230%-8.332%. It can be seen that the absorption effect of this sample is better.

[0081] Example 2

[0082] The difference from Example 1 is that, in step 1, 1000-2000 ml of anhydrous ethanol, 200-300 ml of deionized water, 40-80 ml of ethyl orthosilicate, 70 ml of ammonia water and 0.1 g of potassium chloride are added into a beaker and mixed and stirred to prepare a silica gel solution.

[0083] Step 2: Add 12 g of resorcinol and 16.8 ml of formaldehyde to the silica emulsion, i.e., the silica gel solution, and continue to stir and react to obtain SiO2@RF, which is then ground into powder using a mortar.

[0084] After testing the sample, it can be concluded according to the test results: the reflectivity of the sample in the visible light band (400nm-760nm) is 9.251%-3.549%, while the reflectivity of the commercially available carbon powder as a comparison example in the visible light band (400nm-760nm) is 13.230%-8.332%. It can be seen that the absorption effect of this sample is better.

[0085] Example 3

[0086] The difference from Example 1 is that, in step 1, 1000-2000 ml of anhydrous ethanol, 200-300 ml of deionized water, 40-80 ml of ethyl orthosilicate, 70 ml of ammonia water and 1 g of potassium chloride are added into a beaker and mixed and stirred to prepare a silica gel solution.

[0087] Step 2: Add 4.8 g of resorcinol and 6.72 ml of formaldehyde to the silica emulsion, i.e., the silica gel solution, and continue to stir and react to obtain SiO2@RF, which is then ground into powder using a mortar.

[0088] After testing the sample, it can be concluded according to the test results: the reflectivity of the sample in the visible light band (400nm-760nm) is 3.469%-1.881%, while the reflectivity of the commercially available carbon powder as a comparison example in the visible light band (400nm-760nm) is 13.230%-8.332%. It can be seen that the absorption effect of this sample is better.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A hollow porous carbon ball ultra-black material, characterized in that: The invention comprises phenolic resin, which is synthesized from resorcinol and formaldehyde; resorcinol and formaldehyde are added to a silica gel solution to form a core-shell structure SiO2@RF with silica as a core and phenolic resin as a shell; the core-shell structure SiO2@RF is carbonized in a nitrogen atmosphere at high temperature to convert the phenolic resin shell layer into a carbon shell layer, the silica is removed by an etchant, and holes are formed in the carbon shell layer to obtain a hollow porous carbon ball ultra-black material.

2. The hollow porous carbon ball ultra-black material according to claim 1, characterized in that: The etchant is sodium peroxide.

3. The hollow porous carbon ball ultra-black material according to claim 2, characterized in that: The amount of sodium peroxide used in the process of removing silicon dioxide is excessive.

4. The hollow porous carbon ball ultra-black material according to claim 1, characterized in that: In the silica gel solution, the particle size of silica with different particle sizes can be adjusted in the range of 70 nanometers to 2000 nanometers.

5. The hollow porous carbon ball ultra-black material according to claim 1, characterized in that: The method for preparing the hollow porous carbon ball ultra-black material adopts a hard template method and a chemical etching method in combination.

6. A method for preparing a hollow porous carbon ball ultra-black material, characterized in that: The method is applied to prepare a hollow porous carbon sphere ultra-black material according to any one of claims 1 to 5, and the method comprises the following steps: Step 1, synthesis of silicon dioxide: prepare a silicon dioxide gel solution by a sol-gel method, and adjust the amount of ammonia water and the amount of potassium chloride added according to the required particle size of silicon dioxide to obtain silicon dioxide with different required particle sizes; Step 2, synthesis of SiO2@RF: adding resorcinol and formaldehyde to the silica gel solution, the phenolic resin generated by resorcinol and formaldehyde will adhere to the surface of silica, forming a core-shell structure SiO2@RF with silica as the core and phenolic resin as the shell; Step 3: Carbonization to form SiO2@C: The core-shell structure SiO2@RF is carbonized in a tubular furnace in a nitrogen atmosphere at high temperature, so that the phenolic resin shell layer is converted into a carbon shell layer SiO2@C; Step 4: Removal of silica core: Add excess sodium hydroxide to remove silica in the carbon shell SiO2@C to obtain hollow carbon spheres; Step 5: Sodium hydroxide pore formation: The dried hollow carbon spheres are mixed with sodium hydroxide and reacted at high temperature to form pores to obtain hollow porous carbon spheres.

7. The method for preparing a hollow porous carbon ball ultra-black material according to claim 6, characterized in that: In the step 2, the thickness of the phenolic resin shell can be changed by changing the dosage of resorcinol and formaldehyde, thereby obtaining hollow carbon spheres with different desired shell thicknesses.

8. The method for preparing a hollow porous carbon ball ultra-black material according to claim 6, characterized in that: In the step 5, during the pore-forming process, hollow porous carbon spheres with different pore sizes can be obtained by adjusting relevant parameters.

9. The method for preparing a hollow porous carbon sphere ultra-black material according to claim 8, characterized in that: The relevant parameters include any one or more of the thickness of the carbon sphere shell layer, the temperature of the pore-forming reaction, and the ratio of the hollow carbon sphere to the sodium hydroxide.

10. The method for preparing a hollow porous carbon ball ultra-black material according to claim 8, characterized in that: The pore size range of the hollow porous carbon sphere can be adjusted from micropore to mesopore and then to macropore; the pore size of the micropore is less than 10 nanometers; the pore size of the mesopore is between 10 nanometers and 50 nanometers; and the pore size of the macropore is greater than 50 nanometers.

Citation Information

Patent Citations

  • Preparation method of nitrogen doped hollow mesoporous carbon sphere

    CN105819422A

  • Preparation method of highly dispersed silicon dioxide microsphere with controllable particle size

    CN107285323A

  • Preparation method of wide-waveband super-black paint

    CN109880502A

  • Preparation method of hollow carbon spheres with through mesopores and composite sodium metal negative electrode of hollow carbon spheres

    CN114368738A

  • Method for regulating and controlling growth particle size of silicon dioxide by sol-gel method through surface tension of solution

    CN117208916A

Cited By

  • Preparation method and application of multilayer carbon sphere material

    CN119873798A